2016
DOI: 10.1007/s00417-016-3393-z
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of rabbit sclera after scleral crosslinking with riboflavin and blue light of different intensities

Abstract: The data indicate that in rabbits, scleral crosslinking with riboflavin and blue light of 200 mW/cm(2) for 20 min is relatively safe and does not induce ultrastructural alterations of scleral cells and of the collagen composition of the scleral stroma. Irradiation with blue light of intensities between 200 and 400 mW/cm(2) induces scleral cell activation, which may contribute to scleral scarring and stiffening. Higher intensities cause scleritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Using 450-nm blue light, a damage threshold of 200 to 400 mW/cm 2 for 20 minutes has been established for rabbit sclera. 21,27 In our study, we used 25 to 50 mW/cm 2 irradiation for 30 minutes, much lower than the damage threshold, and yet achieved an increase of greater than 80% in the Young's modulus at 8% strain. SXL-induced changes in elastic moduli can depend greatly on sample preparation and analysis procedure, but our results are generally consistent with previous studies using riboflavin and porcine eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Using 450-nm blue light, a damage threshold of 200 to 400 mW/cm 2 for 20 minutes has been established for rabbit sclera. 21,27 In our study, we used 25 to 50 mW/cm 2 irradiation for 30 minutes, much lower than the damage threshold, and yet achieved an increase of greater than 80% in the Young's modulus at 8% strain. SXL-induced changes in elastic moduli can depend greatly on sample preparation and analysis procedure, but our results are generally consistent with previous studies using riboflavin and porcine eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In eyes treated with scleral cross-linking, but no myopia induction, an inhibition of eye growth is present, further demonstrating the role of scleral cross-links on eye growth cessation (51). In contrast to myopic eyes, when scleral cross-linking is performed in vivo without myopia induction the scleral collagen fibre bundles also become skewed towards smaller diameters (52) and increased variability in fibre bundle composition (53). Biomechanically, the crosslinked sclera shows increased elastic and viscous modulus (53)(54)(55), and increased stiffness (53).…”
Section: Collagen Cross-linkingmentioning
confidence: 89%
“…Increasing levels of irradiation provide, in most cases, greater scleral stiffening, but increasing irradiation levels increase the risk of complications. Scleral inflammation (58), collagen destruction or disorganisation (52,53,55), reduction in dark-adapted electroretinogram (ERG) (54), and retinal cell death and layer disruption (51-54,58) have all been observed following cross-linking procedures, particularly with higher irradiance levels. Given that the biomechanical changes required to prevent myopia progression require higher irradiances to achieve, the potential for serious side effects to occur with current procedures warrants careful further investigation before starting human cross-linking trials.…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…Xia et al 11 used polarized light microscopy and observed a microscopically detectable corneal haze with a significant increase in type III collagen fibrils between 30 and 90 days after crosslinking therapy with riboflavin and ultraviolet light. Karl et al 22 used electron microscopy to examine how the fibrils change after crosslinking and found similar changes in structure with blue light treatment.…”
Section: Discussionmentioning
confidence: 99%